Image de la royauté sacrée dans Le Roi Lion. Étude d'anthropologie historique et politique - Petit, Tierry (Anthropologica, 2022)
From Max Weber to the school called Leyde, anthropological studies pointed to certain number of political, sociological economical and ideological characteristics of early States; later, a certain number of studies in ancient history and in archaeology adopted this hermeneutic model. Most of these traits are present in Walt Disney Studios' film Lion King. The analysis shows that ideological representations of royalty and the substance of power over beings and territory are not random selections but belong to a premodern view of the State.